Outcome after discontinuation of nucleot(s)ide analogues in chronic hepatitis B: relapse rate and associated factors - Kranidioti, Hariklia (Ann Gastroenterol, 2015)
The introduction of nucleot(s)ide analogues (NAs) for oral antiviral therapy has dramatically improved the clinical outcome of patients with chronic hepatitis B. NAs appear to be safe and induce potent suppression of viral replication. However, they are associated with a low rate of HBsAg seroclearance, the gold standard of successful treatment, and also with a relatively high rate of virological relapse after discontinuation. As a result, long-term treatment is needed. The optimal duration of NA treatment currently remains unclear, nevertheless in some patients NA treatment can be stopped with a relatively low probability of relapse. Whether NAs are able to induce a sustained off-treatment response is an important area for research. This article reviews the relapse rate after cessation of treatment with NAs in chronic hepatitis B patients with the goal of identifying possible predictive factors of relapse.